The relationship between passion for coaching and the coaches` interpersonal behaviors: The mediating role of coaches` perception of the relationship quality with athletes - Kim, I.; Lee, K.; Kang, S. (International Journal of Sports Science & Coaching, 2019)
According to Self-Determination Theory, sports coaches` autonomy-supportive behaviors positively influence athletes` different aspects, such as motivation, well-being, and performance, while controlling behaviors of coaches tend to diminish such variables. Although many researchers agree that autonomy-supportive coaching style should be promoted rather than a controlling style, there is scarce research investigating the antecedents of such behavioral styles. The aim of this study was to examine a model of potential determinants of coaches` interpersonal behaviors by investigating the relationship between passion for coaching and their behavioral styles and verifying the mediating role of coaches` perceived relationship quality with their athletes. A total of 172 coaches participated in the survey, and data sets were analyzed using structural model analysis. Results revealed that coaches` harmonious passion positively predicted autonomy-supportive behaviors but negatively predicted controlling behaviors, and these pathways were mediated by coaches` perception of the relationship with their athletes. The implications for coaches and researchers from those results are discussed.